Is a Bent Crystal Still a Single Crystal?. Issue 30 (29th April 2019) - Commins, Patrick; Karothu, Durga Prasad; Naumov, Panče
Abstract: The mention of the word "crystal" invokes images of minerals, gems, and rocks, all of which are inevitably solid, hard, and durable entities with well‐defined smooth faces and straight edges. With the discovery in the first half of the 20th century that many molecular crystals are soft and can be deformed in a similar way as rubber or plastic, this perception is changing, and both the concept and formal definition of what a crystal is may require reinterpretation. The seemingly naïve question posed in the title of this Minireview does not have a simple answer. Here, we discuss how the effects of the elastic and plastic deformation of molecular crystals on the diffraction signature give primary evidence of their degree of crystallinity. In most cases, the definition of a crystal holds for both elastically and plastically deformed crystals and, unless there is significant or complete physical separation of the crystal during the deformation, they can safely be considered (deformed) single crystals with a high concentration of defects. Abstract : Crystal clear? The ambiguity related to the single‐crystal nature of elastically and plastically deformable crystals as well as the correct use of the terms "single crystal/crystalline" and "polycrystal/crystalline" are clarified in this Minireview with selected examples of recently reported bending molecular crystals.